EFEKTIVITAS PENERAPAN PENGENDALIAN INTERN PADA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KOTA BANDUNG - Kamalah Saadah (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2019)
Competition during the ASEAN Economic Community (MEA) encourages all business units to be able to optimize their performance. Actors of MSMEs (Micro, Small and Medium Enterprises) which have a large contribution to the nation's economy need to look at internal controls on their entities so they can have competitiveness. This study aims to determine the internal control applied by MSMEs in the city of Bandung. This has become important to observe given the different characteristics of MSMEs with large companies, especially in terms of the number of workers and the division of tasks. A series of questionnaires in the form of a number of questions regarding internal control for small entities will be filled by MSME respondents to find out the description of internal control practices in MSMEs. The method used in this study is a quantitative method with a descriptive approach which in this study will be described regarding internal control of MSMEs in the city of Bandung. The results of the study show that in general the effectiveness of internal controls implemented by MSMEs in Bandung is considered quite good. This allows researchers to propose recommendations as a consideration for planning internal control strategies for MSME activists in general.